Analysis of Pharmacotherapy Costs and Outcome of Treatment of Hospitalized Patients with COVID-19: Analysis of Pharmacotherapy costs of COVID-19 - Hayati, Hadi (Iranian Journal of Pharmaceutical Sciences, 2024)
The COVID-19 pandemic has significantly affected people's lives and healthcare systems worldwide. Therefore, it is important to determine its effects on the economic and health sectors. This study aimed to calculate and analyze the costs and outcomes of COVID-19 treatment, including mortality and recovery, to improve health system planning. This cross-sectional descriptive study analyzed the costs and consequences of COVID-19 treatment in one of the largest referral training centers for patients in Lorestan province, Iran. The study examined hospital documents from the beginning of January to the end of December 2022. The results showed that the recovery rate of patients was approximately 87%, and the average cost per patient was 161 USD. More than 70% of this cost was related to medication and hospital bed expenses. Lopinavir was the most prescribed medication, and Immunoglobulin and Remdesivir had the highest cost share among all medication expenses. Given the significant proportion of medication and hospitalization expenses, it is recommended that the new approach to prescribing medications and managing patient care should be centered around standardized treatment protocols and home-based care. This is particularly crucial in developing countries with limited resources and clinical evidence. It is important to note that the calculation of standard treatment costs has limitations and should be interpreted cautiously.